STUDYING THE PREVALENCE AND NEGATIVE IMPACT OF DIFFERENT TYPES OF TOBACCO PRODUCTS ON ADOLESCENT HEALTH - D.O. Klymko (Проблеми екології та медицини)
Introduction. Recently, alternative forms of tobacco use, particularly electronic devices for heating tobacco (vapes), have gained significant popularity among adolescents. The aim of the study was to analyze the prevalence of tobacco product use among adolescents, including those with a history of bronchopulmonary disease, and to assess the impact of tobacco use on adolescent health. Materials and methods. A total of 1,280 adolescents aged 12 to 17 years were surveyed using a one-step anonymous questionnaire. The study was conducted in accordance with the principles outlined in the Declaration of Helsinki. The study protocol received approval from the Local Ethics Committee of all participating institutions. Informed consent was obtained from the parents or guardians of the participants. Data analysis was performed using STATISTICA for Windows 10 Pro. Results. The results of the survey revealed that tobacco product use among adolescents was twice as high in boys compared to girls, aligning with findings from other studies. Vapes were the most commonly used tobacco product, reported by 70.77% of girls and 51.54% of boys who used tobacco. Analysis of the data also showed a history of bronchopulmonary pathology among respondents: over half (67%) had experienced bronchitis, 23.5% had pneumonia, 4.5% had allergic rhinitis, and 5% had bronchial asthma. Despite these conditions, many continued to use various types of tobacco products. While recent research has increasingly focused on pulmonary fibrosis in adult patients, similar studies remain lacking in the pediatric population. Conclusions. Developing diagnostic methods for detecting pulmonary fibrosis in pediatric patients with bronchial asthma is crucial, as it enables early identification of fibrotic changes, slows disease progression, and enhances the quality of life in affected children.